Determination of the numerical parameters of a continuous damage model for the structural analysis of clay brick masonry - Mangueira, Felipe Barbosa [UNESP]; Oliveira Neto, Luttgardes de [UNESP]; Azambuja, Maximiliano dos Anjos [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2012)
Models based on the continuous damage theory present good responses in representing the nonlinear behavior of reinforced concrete structures with loss of strength and stiffness of the material. However, damage theory is rarely employed in the analysis of masonry structures and numerical simulations are currently performed mostly by Finite Element Method formulations. A computational program was designed to determine the numerical parameters of a damage model of the physical properties of masonry components, solid clay brick and mortar. The model was formulated based on the composition of tensile and compressive surface strengths in the plane stress state. The numerical parameters, the corresponding curves of the activation surfaces and the evolution of the surfaces are presented. The results were fed into the computational program based on the Boundary Element Method (BEM) for the simulation of masonry walls, and two types of masonry were simulated. The results confirm the good performance of the model and the program based on the BEM.
Keywords: damage model; numerical parameters; clay brick masonry; BEM